Association Between Oral Health Status and Quality of Life Among Patients with Diabetes Mellitus - Henny Febriani; Wirza Wirza; Reca Reca; Cut Aja Nuraskin (PT. Riset Press International, 2026)
Oral health constitutes an essential component of overall health; however, individuals with diabetes mellitus (DM) are at increased risk of developing oral diseases due to metabolic dysregulation and chronic inflammation, which may substantially impair their quality of life. This study aimed to evaluate oral health status and oral health–related quality of life (OHRQoL) among hospitalized patients with DM and to examine the associations between these variables. A quantitative cross-sectional study was conducted at TK II Iskandar Muda Hospital, Banda Aceh, Indonesia, between July 21 and August 8, 2025. A total of 67 hospitalized patients with DM were recruited using accidental sampling. Oral health status was assessed through clinical examinations, including the Decayed, Missing, and Filled Teeth (DMF-T) index, Oral Hygiene Index–Simplified (OHI-S), and periodontal status assessment. OHRQoL was measured using a structured questionnaire. Data were analyzed using univariate statistics and bivariate analysis with the Chi-square test. Most respondents were aged 50–69 years (56.71%). A high burden of oral health problems was observed, with 62.7% of participants exhibiting very high DMF-T scores, 70.1% presenting with poor oral hygiene, and 59.7% having poor periodontal status. Consistently, 70.1% of respondents reported a low OHRQoL. Bivariate analysis demonstrated statistically significant associations between OHRQoL and dental caries status (p = 0.035), oral hygiene status (p = 0.006), and periodontal status (p = 0.0001). Poor oral health status is significantly associated with reduced quality of life among hospitalized patients with diabetes mellitus. Periodontal status showed the strongest association with OHRQoL, underscoring the critical need for integrated oral health management and targeted educational interventions as part of comprehensive diabetes care to enhance patients’ overall well-being.